Pathological mechanism of chondrocytes and the surrounding environment during osteoarthritis of temporomandibular joint - Li, Baochao; Guan, Guangzhao; Mei, Li; Jiao, Kai; Li, Huang (Journal of cellular and molecular medicine, 2021)
Temporomandibular joint (TMJ) osteoarthritis is a common chronic degenerative disease of the TMJ. In order to explore its aetiology and pathological mechanism, many animal models and cell models have been constructed to simulate the pathological process of TMJ osteoarthritis. The main pathological features of TMJ osteoarthritis include chondrocyte death, extracellular matrix (ECM) degradation and subchondral bone remodelling. Chondrocyte apoptosis accelerates the destruction of cartilage. However, autophagy has a protective effect on condylar chondrocytes. Degradation of ECM not only changes the properties of cartilage but also affects the phenotype of chondrocytes. The loss of subchondral bone in the early stages of TMJ osteoarthritis plays an aetiological role in the onset of osteoarthritis. In recent years, increasing evidence has suggested that chondrocyte hypertrophy and endochondral angiogenesis promote TMJ osteoarthritis. Hypertrophic chondrocytes secrete many factors that promote cartilage degeneration. These chondrocytes can further differentiate into osteoblasts and osteocytes and accelerate cartilage ossification. Intrachondral angiogenesis and neoneurogenesis are considered to be important triggers of arthralgia in TMJ osteoarthritis. Many molecular signalling pathways in endochondral osteogenesis are responsible for TMJ osteoarthritis. These latest discoveries in TMJ osteoarthritis have further enhanced the understanding of this disease and contributed to the development of molecular therapies. This paper summarizes recent cognition on the pathogenesis of TMJ osteoarthritis, focusing on the role of chondrocyte hypertrophy degeneration and cartilage angiogenesis.